1991
DOI: 10.3168/jds.s0022-0302(91)78548-2
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Hypocalcemia at First Parturition in Norwegian Cattle: Genetic Correlations with Yield and Weight

Abstract: Minimum plasma calcium level around parturition and its relation to BW at parturition, milk yield, and weight change in mo 1 of lactation were studied in 334 first lactation Norwegian cows. Minimum plasma calcium level was reached 18 to 30 h postpartum. Single observations for all animals were fitted with a multitrait animal model including all genetic relationships. Heritabilities of the traits were calcium postpartum, .11; milk yield, .35; BW, .65; and weight change, .17 with standard errors about .10. Genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
3
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 18 publications
3
13
3
4
Order By: Relevance
“…The 95% HPDR did not include 0 ( Table 2) for mixed inheritance (polygene + major gene) heritability. Karacaören et al (2006) found 340 B. Karacaören et al Tveit et al (1991) or 0.64 by Svendsen et al (1994), agreed with our results. In general, there are no literature estimates on mixture inheritance model heritabilities for MY, DMI, and BW in dairy cattle, and hence our results cannot compared; while for MS the mixed heritabilities were reported to be higher than polygenic heritabilities (Ilahi and Kadarmideen 2004).…”
Section: Point Estimates Of Mixed Inheritance Model Heritabilitiessupporting
confidence: 83%
“…The 95% HPDR did not include 0 ( Table 2) for mixed inheritance (polygene + major gene) heritability. Karacaören et al (2006) found 340 B. Karacaören et al Tveit et al (1991) or 0.64 by Svendsen et al (1994), agreed with our results. In general, there are no literature estimates on mixture inheritance model heritabilities for MY, DMI, and BW in dairy cattle, and hence our results cannot compared; while for MS the mixed heritabilities were reported to be higher than polygenic heritabilities (Ilahi and Kadarmideen 2004).…”
Section: Point Estimates Of Mixed Inheritance Model Heritabilitiessupporting
confidence: 83%
“…Heritability estimates for serum Ca concentration in Holsteins after calving are lacking. Only one study investigated the genetic variation of Ca concentration in Norwegian Reds cows and reported a low heritability (0.11 ± 0.09) that was not statistically different from zero (Tveit et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Serum Ca, P, Mg, and K concentrations are influenced by environmental factors, mainly nutrition (NRC, 2001;Kronqvist, 2011). Nutritional and management strategies for the prevention of these macromineral deficiencies have been developed (Bethard et al, 1998;Tauriainen et al, 2003;Rérat et al, 2009); however, a genetic component to these traits also exists, as reported for serum Ca concentration by Tveit et al (1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypocalcemia occurs because Ca leaves the extracellular fluid pool to enter the mammary gland faster than it can be replaced by intestinal Ca absorption or bone Ca resorption (Goings et al, 1974;Jorgensen, 1974;Goff and Horst, 1997). Low blood calcium can be explained by increasing cortisone and estrogen levels in blood and decreasing receptor number of D vitamin in intestine during parturition (Horst et al, 1989;Tveit et al, 1991).…”
Section: Introductionmentioning
confidence: 99%